Ceftaroline Fosamil (CPT) vs. Vancomycin (VAN) for Acute Bacterial Skin and Skin Structure Infections (ABSSSI). (4th October 2017) - Trinh, Trang D; Zasowski, Evan J; Claeys, Kimberly; Lagnf, Abdalhamid M; Delaportas, Dino; Estrada, Sandy; Davis, Susan L; Klinker, Kenneth; Huang, Vanthida; Kaye, Keith S; Bonine, Nicole; Gillard, Patrick; et al.
Abstract: Background: Hospital visits for ABSSSIs are rising. Inadequate treatment results in longer stays and increased recurrences. Intravenous (IV) antibiotics (e.g., VAN) are commonly used for ABSSSIs. CPT is approved for ABSSSI, though real world clinical comparative data is limited. The study objective was to compare infection-related length of stay (LOSIR ) for CPT vs. VAN for ABSSSI. Methods: We conducted a retrospective, multicenter, propensity-matched cohort study from January 1, 2012 to June 1, 2016 using variable matching ratios. Patients were matched on time to study drug and acute kidney injury (AKI) present on admission (POA). Patients included were adults ≥18 years old with ABSSSI diagnosis and ≥3 clinical signs requiring ≥72 hours CPT or VAN started ≤120h of ABSSSI diagnosis. Patients were excluded if they had osteomyelitis, other infection sources, irremovable hardware, or >120h prior ABSSSI treatment. LOSIR was defined as LOS following ABSSSI diagnosis. Multivariable linear regression examined the independent association between treatment and LOSIR . Results: A total of 311 patients were matched (119 CPT and 192 VAN). The mean (±standard deviation (SD)) age was 58 (±18) years, 61% Caucasian, 57% male, median (interquartile range (IQR)), Charlson Comorbidity Index (CCI) and LOSIR were 2 (1, 3) and 6 (4, 9) days, respectively. Common comorbid conditions were diabetes (38%), peripheral vascular disorders (24%), and chronic pulmonary disease (26%). With regard to ABSSSI, 54% had cellulitis, 48% was lower extremity, 21% had methicillin-resistant Staphylococcus aureus, 64% did not have surgical interventions, 55% were deescalated from IV to oral antibiotics. The median (IQR) of LOSIR for CPT and VAN groups were 5 (4, 8) and 7 (4, 10) days, P = 0.007, respectively. Compared with VAN, CPT was associated with shorter LOSIR after adjusting for ABSSSI type, SIRS criteria, CCI, and AKI POA (P = 0.013). Conclusion: Compared with VAN, ABSSSI patients treated with CPT had significantly shorter LOSIR . Early CPT use may be considered for patients who need IV antibiotics for ABSSSI treatment to facilitate early discharge. Additional studies are needed to confirm these findings. Disclosures: D. Delaportas, Allergan: Speaker's Bureau, Speaker honorarium; S. L. Davis, Allergan: Grant Investigator and Scientific Advisor, Consulting fee and Research grant; K. Klinker, The Medicines Compnay: Scientific Advisor, Consulting fee; K. S. Kaye, Allergan: Consultant, Consulting fee; N. Bonine, Allergan: Employee, Salary; P. Gillard, Allergan: Employee, Salary; M. J. Rybak, Allergen: Scientific Advisor, Consulting fee